Recommendations on the management of pudendal nerve entrapment syndrome: A formalised expert consensus. (13th October 2021) - Levesque, Amélie; Bautrant, Eric; Quistrebert, Virginie; Valancogne, Guy; Riant, Thibault; Beer Gabel, Marc; Leroi, Anne‐Marie; Jottard, Katleen; Bruyninx, Luc; Amarenco, Gerard; Quintas, Lara; Picard, Pascale; et al.
Abstract: Background: Since the development and publication of diagnostic criteria for pudendal nerve entrapment (PNE) syndrome in 2008, no comprehensive work has been published on the clinical knowledge in the management of this condition. The aim of this work was to develop recommendations on the diagnosis and the management of PNE. Methods: The methodology of this study was based on French High Authority for Health Method for the development of good practice and the literature review was based on the PRISMA method. The selected articles have all been evaluated according to the American Society of Interventional Pain Physicians assessment grid. Results: The results of the literature review and expert consensus are incorporated into 10 sections to describe diagnosis and management of PNE: (1) diagnosis of PNE, (2) patients advice and precautions, (3) drugs treatments, (4) physiotherapy, (5) transcutaneous electrostimulations (TENS), (6) psychotherapy, (7) injections, (8) surgery, (9) pulsed radiofrequency, and (10) Neuromodulation. The following major points should be noted: (i) the relevance of 4+1 Nantes criteria for diagnosis; (ii) the preference for initial monotherapy with tri‐tetracyclics or gabapentinoids; (iii) the lack of effect of opiates, (iv) the likely relevance (pending more controlled studies) of physiotherapy, TENS and cognitive behavioural therapy; (v) the incertitudes (lack of data) regarding corticoid injections, (vi) surgery is a long term effective treatment and (vii) radiofrequency needs a longer follow‐up to be currently proposed in this indication. Conclusion: These recommendations should allow rational and homogeneous management of patients suffering from PNE. They should also allow to shorten the delays of management by directing the primary care. Significance: Pudendal nerve entrapment (PNE) has only been known for about 20 years and its management is heterogeneous from one practitioner to another. This work offers a synthesis of the literature and international experts' opinions on the diagnosis and management of PNE.